Novel insights into the immune cell landscape and gene signatures in autism spectrum disorder by bioinformatics and clinical analysis - Li, Hongwei; Xu, Yiran; Li, Wenhua; Zhang, Lingling; Zhang, Xiaoli; Li, Bingbing; Chen, Yiwen; Wang, Xiaoyang; Zhu, Changlian (Frontiers in Immunology, 2023)
The pathogenesis of autism spectrum disorder (ASD) is not well understood, especially in terms of immunity and inflammation, and there are currently no early diagnostic or treatment methods. In this study, we obtained six existing Gene Expression Omnibus transcriptome datasets from the blood of ASD patients. We performed functional enrichment analysis, PPI analysis, CIBERSORT algorithm, and Spearman correlation analysis, with a focus on expression profiling in hub genes and immune cells. We validated that monocytes and nonclassical monocytes were upregulated in the ASD group using peripheral blood (30 children with ASD and 30 age and sex-matched controls) using flow cytometry. The ROC curves of the four genes showed that they had diagnostic value (PSMC4 and ALAS2) and predictive value (LIlRB1 and CD69) using the “training” and verification groups. Three immune cell types – monocytes, M2 macrophages, and activated dendritic cells – had different degrees of correlation with 15 identified hub genes. In addition, we analyzed the miRNA-mRNA network and drug-gene interactions using miRNA databases (TarBase and miRDB) and the DSigDB database. Two miRNAs (miR-342-3p and miR-1321) and eight drugs (resveratrol, vitinoin, vitamin E, retinoic acid, genistein, cyclosporin A, decitabine, and selenium) were predicted as potential ASD-related therapeutic agents. These findings suggest that dysregulation of the immune system may contribute to ASD development, especially dysregulation of monocytes and monocyte-derived cells. ASD-related hub genes may serve as potential biomarkers for the early diagnosis of ASD, and the potential ASD-related drugs identified here may open up new therapeutic opportunities for ASD.